An Efficient Method for the In Vitro Production of Azol(in)e‐Based Cyclic Peptides1. Issue 51 (21st October 2014) - Houssen, Wael E.; Bent, Andrew F.; McEwan, Andrew R.; Pieiller, Nathalie; Tabudravu, Jioji; Koehnke, Jesko; Mann, Greg; Adaba, Rosemary I.; Thomas, Louise; Hawas, Usama W.; Liu, Huanting; Schwarz‐Linek, Ulrich; et al.
Abstract Heterocycle‐containing cyclic peptides are promising scaffolds for the pharmaceutical industry but their chemical synthesis is very challenging. A new universal method has been devised to prepare these compounds by using a set of engineered marine‐derived enzymes and substrates obtained from a family of ribosomally produced and post‐translationally modified peptides called the cyanobactins. The substrate precursor peptide is engineered to have a non‐native protease cleavage site that can be rapidly cleaved. The other enzymes used are heterocyclases that convert Cys or Cys/Ser/Thr into their corresponding azolines. A macrocycle is formed using a macrocyclase enzyme, followed by oxidation of the azolines to azoles with a specific oxidase. The work is exemplified by the production of 17 macrocycles containing 6–9 residues representing 11 out of the 20 canonical amino acids.